Conjunto de heurísticas para avaliação de usabilidade nas plataformas de streaming de vídeos em dispositivos móveis com foco para as habilidades dos usuários idosos - Salvador, Lilían das Mercês (2021)
Population aging is an expressive sociodemographic transformation of the 21st century. In Brazil, the increase in the number of elderly people and the use of the internet as a form of entertainment can be observed in some works in the literature. In these works, it is possible to observe that one of the most common cultural activities among internet users is the use of streaming videos. This more assiduous use of video streaming services is reaching not only the young, but also the elderly. However, it is noticeable the different way that seniors perceive technology compared to digital natives. As a result, it is necessary to understand the difficulties faced by this audience while browsing these platforms, in order to help promote a more equal and accessible use of video streaming platforms for elderly users. To address this problem, this work proposes the development of a set of specific heuristics to assess the usability of applications in the domain of streaming videos on mobile devices, targeting the elderly audience. From the results obtained by an exploratory study and by completing a checklist that helped in the process of evaluating the usability of the three platforms (YouTube, Globoplay and Netflix) with elderly users, it was possible to observe that the analyzed platforms have some usability problems, mainly, in the categories of “colors and size”, “correction”, “accessibility” and “audiovisual content and layout”, which ended up making navigation difficult for these elderly users.